Managing Trust In The Implementation Network Of Food Diversification Policy In South Sulawesi Province - Novayanti Sopia Rukmana (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This study is motivated by the phenomenon of regional food security. Food diversification policy is one of the efforts to fulfill sufficient, decent quality and safe food, which is based on optimizing utilization and based on the diversity of local resources. this is not in line with the fact that the level of regional food demand is greater than the existing supply. The rapidly increasing demand is the effect of increasing population, economic growth, increasing people's purchasing power and changing tastes in society. This study aims to analyze and describe the management of trust between actors in the implementation network of food diversification policies in South Sulawesi Province. This type of research is a descriptive method with a qualitative research approach. The results of this study indicate that the implementation of food diversification policies has not been effective, this is due to the process of cooperation and coordination of actors in the implementation network of food diversification policies that have not been implemented properly.